Organic chemistry - Carey, Francis A., 1937-; Giuliano, Robert M., 1954-; Allison, Neil T. (Neil Thomas), 1953-; Tuttle, Susan L. Bane (New York, NY : McGraw Hill Education, 2024)
"In this edition the text is organized according to functional groups-structural units within a molecule that are most closely identified with characteristic properties. Reaction mechanisms are emphasized early and often in an effort to develop the student's ability to see similarities in reactivity across the diverse range of functional groups encountered in organic chemistry. Mechanisms are developed from observations; thus, reactions are normally presented first, followed by their mechanism"--
Includes index.
Ages 18+
Grades 10-12
PHR
Karim International
Book Finder International
Keywords: Chemistry, Organic; Chemistry, Organic -- Textbooks; Pharmacy